Caracterización de la comercialización de los pequeños productores maiceros en el cantón Ventanas - Acosta Troya, Jean Carlos (2021)
The present research work, corresponding to the practical component of a complex examination, qualification modality, analyzes, commercialization of small corn producers in the canton Ventanas, with the aim of proposing mechanisms that contribute to improving the conditions of the commercialization chain for the small farmer. For this analysis, bibliographic information was collected from books, magazines, newspapers, scientific articles, web pages, indexed scientific journals, presentations, conferences, technical manuals and expert judgment through virtual means. The information obtained was captured through the techniques of analysis, synthesis and summary, in order for the reader to know the importance of corn production in the family economy of farmers in the Ventanas canton. At the end of the work, the result was the existence of a deficient characterization in the marketing chain of small corn producers with little controlled links, farmers are harmed at the time of marketing their production by receiving inappropriate prices affecting their level of entry.